Selected heavy metals concentrations on selected samples of Naboomspruit, Tobiasspruit and the Nyl floodplain, South Africa. - Sekwele, Ramogale Charles (My University, 2008)
The National Water Act (Act No. 36 of 1998) requires effective use of our water resources for protection of the environment and provision of safe water for current and future generations. Previous studies in the study area have shown that there are certain heavy metals occurring at elevated concentrations. These metals are cadmium, lead,zinc, copper and chromium. Metals tend to increase in concentrations in organisms at higher trophic levels through a process called bioaccumulation and this was assessed during the study. There is very little data on the tributaries of this system because the streams flow intermittently. Less attention has in the past been given to these smaller streams yet they contribute a great deal to larger rivers of interest. This study focused on Naboom Spruit and Tobias Spruit, both tributaries of the Mogalakena River. The study was to determine the levels of certain selected metals within the system and to prove the hypothesis that wetlands act as pollutant filters. The study was also undertaken to further assess levels of those metals which have been recorded to be occurring at high concentration in certain areas within the Mogalakwena River system. A supplementary fish exposure laboratory experiment to determine the rate of uptake of cadmium and zinc by Clarias gariepinus in vitro under controlled conditions was also undertaken.Both the high and low flow surveys were conducted where physico-chemical parameters were recorded on sites and water, fish, aquatic macro-invertebrates, sediment and aquatic plants were collected. These samples were analysed for cadmium, lead, zinc,copper and chromium content using methods described in chapter 3 of the study. The laboratory fish exposure experiment followed the analytical protocol described in Chapter 7 of this document. Results obtained were statistically analysed and recorded and of the five metals studied in this project, the mean concentrations in all samples at the studied reaches of the subcatchment ranked: Zinc>Copper>Chromium>Lead>Cadmium. The ranking for samples is generally: sediment>invertebrates>fish>plants. The hypothesis that sediment tend to have increased free and compound heavy metals was clearly depicted in this study. There was increase in metal concentrations in sediment samples also increased on sites where there was less or no flow as a result of lower turbulence. In general, metal contents between sites ranked: Driefontein>Mine>Tobias>Bergland>Sacchariasboom. Metal concentrations were low at Bergland, increasing downstream and after the vlei area decreasing to as little as in the headwater at Sacchariasboom. It was then deduced that the vlei area plays its important role as a filter for pollutants in the natural system as the Sacchariasboom site is downstream of a wetland area after confluence of the Tobias Spruit with the Nylsvley. All concentrations of the five metals studied were higher in the other fish species as compared to values measured in C. gariepinus. These seem to relate perfectly to the low concentration of all the metals in Sacchariasboom site, where the C. gariepinus analysed for metals were collected. It is often difficult to determine in the natural environment, which factor/s in the system affects concentrations of other metals and substance, and which one causes a problem,because of multiple occurrences. Laboratory tests such as metals exposure to biota under set conditions was used in this study to determine synergistic and or additive effects of all components in a natural system. Under conditions of the experiment performed in this study, zinc showed to have higher affinity and or was taken up much quicker by C. gariepinus than cadmium, both in pure metal (zinc or cadmium alone) and combination of metal(zinc/cadmium solution), under similar conditions. Zinc has therefore proved to have higher binding affinity to proteins of the fish than cadmium under the set condition in this experiment.
Thesis (M.Sc) -- University of Limpopo, 2008.
Keywords: Metals; 669.0968; Metallurgy